1986
DOI: 10.1002/jcp.1041290303
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclasts and osteoblasts migrate in opposite directions in response to a constant electrical field

Abstract: We have investigated in vitro the effects of the electrical field produced by constant current on freshly isolated rabbit osteoclasts and on well characterized clonal rat osteoblastlike cells. At field strengths of 0.1 and 1 V/mm, the osteoclasts migrated rapidly toward the positive electrode, whereas the osteoblastlike cells migrated in the opposite direction, toward the negative electrode. Thus, different cell types from the same tissue can respond differently to the same electrical signal. These results hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(89 citation statements)
references
References 27 publications
4
80
1
1
Order By: Relevance
“…Consequently, for bone regeneration, these cells communicate with other bone cells, such as osteoblasts and osteoclasts. The influence of electrical stimulation on bone healing has been studied in vitro [60][61][62][63][64][65][66] and in vivo [67][68][69][70][71][72] and it has been demonstrated that the application of these stimulus can enhance and stimulate osteogenic activities. In this way, the osteoblasts are affected by electromechanical signals to apposite bone tissue [73][74], the piezoelectric nature of bone, leading to natural conversion of the mechanical stimuli into electrical ones.…”
Section: Bonementioning
confidence: 99%
“…Consequently, for bone regeneration, these cells communicate with other bone cells, such as osteoblasts and osteoclasts. The influence of electrical stimulation on bone healing has been studied in vitro [60][61][62][63][64][65][66] and in vivo [67][68][69][70][71][72] and it has been demonstrated that the application of these stimulus can enhance and stimulate osteogenic activities. In this way, the osteoblasts are affected by electromechanical signals to apposite bone tissue [73][74], the piezoelectric nature of bone, leading to natural conversion of the mechanical stimuli into electrical ones.…”
Section: Bonementioning
confidence: 99%
“…As far as how the ES signal induced the cytoskeletal reorganization to be large enough to cause significant change in cell shape, the authors attributed it to the change of intracellular free calcium levels. In another study, Ferrier et al (Ferrier et al, 1986) cultured rabbit osteoclasts and rat osteoblast-like cells on glass coverslips in field strengths of 0.1 and 1 V/mm and found that the osteoclasts migrated rapidly toward the positive electrode, while the osteoblast-like cells migrated in the opposite direction toward the negative electrode, showing that different types of bone cells respond differently to the same electrical signal. When salt bridges are used, the so-called faradic products, including hydrogen peroxide, hydroxyl and oxygen ions, free radicals, and other intermediates, are excluded from the culture medium.…”
Section: Salt Bridgementioning
confidence: 99%
“…Galvanotaxis and galvanotropism (i.e. EF-mediated migration and shape change, respectively) occur in keratinocytes, epithelial cells, bone cells, chondrocytes and fibroblasts (Chao et al, 2000;Ferrier et al, 1986;Sheridan et al, 1996;Soong et al, 1990;Zhao et al, 1996a). The EF strengths commonly used (1-10 V cm -1 ) are physiologically significant for vertebrates, because 1-2 V cm -1 gradients have been measured on either side of the cut surface of wounds owing to ion flux through leaky cell membranes (Soong et al, 1990) or transepithelial potential driven by Na + pumps (Vanable, 1989).…”
Section: Cdc42 and Its Downstream Effectorsmentioning
confidence: 99%